Differences in perceived threat and trauma in children during the COVID-19 pandemic - Gabriele Kohlboeck; Anna Wenter; Kathrin Sevecke; Silvia Exenberger (BMC, 2023)
Abstract Background The past 2 years of the COVID-19 pandemic were stressful for most children and adolescents; some children may have experienced a high level of stress and trauma. To date, no study has examined self-reported stress and trauma levels due to COVID-19 in children. This study aimed to assess perceived threat, exposure and trauma symptoms in children aged 7-13 years. In addition, we explored whether parent-reported factors could predict a higher risk of COVID-19 vulnerability in their children. Method Cross-sectional data were collected from 752 children to assess COVID-19 threat, exposure and trauma symptoms using the self- and parent-reported Child and Adolescent Trauma Screening Self-Report (CATS) Trauma questionnaire. We used exploratory analyses (factor analysis of mixed data and hierarchical clustering) to identify subgroups (i.e., clusters) of children sharing similar characteristics in the dataset. Linear regression modeling was applied to determine the likelihood of higher threat and vulnerability in children with parent-reported COVID-19 threat, exposure, CATS trauma symptoms, behaviors on the Child Behavior Checklist (CBCL), and posttraumatic growth (PTG). Results We identified a high-risk group of children reporting clinically relevant trauma symptoms and COVID-19-related fears. Parents' reports of trauma could be used to identify children at high risk. Conclusions Approximately 25% of children reported moderate to clinically relevant levels of trauma symptom. It is especially important to offer adequate support to these children to ease the trauma and prevent their symptoms from developing into psychopathology.